Synthesis and biological activity of 4-thiazolidinones, thiosemicarbazides derived from diflunisal hydrazide - (:unkn) unknown (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2006)
Two novel series of 4-thiazolidinone derivatives, namely 2',4'-difluoro-4-hydroxybiphenyl-3-carboxylic acid [2-(5-nitro-2-furyl/substituted phenyl)-4-thiazol idinone-3 -y1jam ides (5a-g) and 2-(2',4'-difluoro4-hydroxybipheiiyl-3-carbonylhydrazono)-3-alkyl/ary1-4-thiazolidinones (6ae) together with 5-(2',4'-difluoro4-hydroxybiphenyl-5-yi)-2-cyclohexylamino-1,3,4-oxadiazole (7a) have been synthesized as title compounds. 1-(2',4'-Difluoro-4-hydroxybiphenyl-3-carbonyl)4-alkyl/atylthiosemicarbazides (4a-g) were also obtained and used as intermediate to give the title compounds. All synthesized compounds were screened for their antimycobacterial activity against Mycobacterium tuberculosis H37Rv, antiviral and antimicrobial activities against various virus, bacteria and fungi strains. (c) 2006 Elsevier SAS. All rights reserved.
Keywords: 4-thiazolidinone; anti-HIV activity; diflunisal; thiosemicarbazide; MYCOBACTERIUM-TUBERCULOSIS; DERIVATIVES; THIAZOLIDINONES; 1,3,4-OXADIAZOLES; HYDRAZONES; INHIBITORS; AGENTS; ASSAY; AIDS